STUDY OF ANTI-ULCEROGENIC EFFECT OF METHANOL EXTRACT AND FRACTIONS OF THE LEAVES OF OCIMUM GRATISSIMUM (LAMIACEAE), ON ETHANOL-INDUCED ULCER IN RATS (FUDMA JOURNAL OF SCIENCES, 2023)
Peptic ulcer has been a ravaging gastrointestinal disorder in clinical practice. The symptomatic effect is the perforation of the stomach lining. The study was aimed at evaluating the anti-ulcer activity and phytochemical constituents of the leaves of Ocimum gratissimum The powdered leaves were macerated in 95%v/v of methanol for 72 h, and the dried extract obtained was washed with n-hexane (Hex), ethyl acetate (EtOAc) and butanol (Buta) successively using the solvent partition method to fractionate. Phytochemical constituents were evaluated using validated methods. Acute toxicity was performed using a modified Lorke’s method. Antiulcer studies were conducted using an ethanol-induced ulcer in the rat model. The rats received 200, 400 and 20 mg per kg body weight of Ocimum .gratissimum extract, its fractions and omeprazole respectively once daily for 14 days. The extraction yielded 3.3 % methanol extract, 16.8 % n-hexane 24.4 % ethyl acetate and 5.2 % butanol fractions. The phytochemical constituents of the extracts are alkaloids, flavonoids, tannins, terpenoids, carbohydrates, steroids and saponin. There was no mortality even at an oral dose of 5000 mg of extract/kg of mouse in the acute toxicity evaluation. The extract and its fractions (200 and 400 mg/kg doses) exhibited dose-dependent ulcer curative. The Hex fraction (400 mg/kg) demonstrated the best anti-ulcer effect with 78.5 % and ulcer index (UI) of 0.60±0.24 when compared to the standard with 50% and 1.40±0.24 respectively. A significant reduction (p< 0.05) in the UI was observed in rats treated with the Ocimum. gratissimum extract and its fractions.
Keywords: anti-ulcer; ethanol-induced ulcer; Ocimum gratissimum; Omeprazole; peptic ulcer; toxicity; rats